Impact of COVID-19 lockdown on children with neurodevelopmental disorders - Mariana Eiras Dias; Melissa Brigham Figueiredo; Laura Azurara; Raquel Marta (Publicaciones Permanyer, 2024)
Introduction and objectives: Neurodevelopmental disorders (ND) affect the maturation of the central nervous system, leading to abnormal brain functioning which may affect a child's social, cognitive, and emotional capacities. The coronavirus disease 2019 (COVID-19) pandemic, and particularly the lockdown period, resulted in indisputable changes in the lives of children, especially those with disabilities. The purpose of this study is to determine the impact of the lockdown period on these children and their parents in terms of therapies, mental and physical health, isolation, school performance, and the impact on family dynamics and relationships. Methods: A cross-sectional study compared the effect of the COVID-19 pandemic lockdown on the health of children with neurodevelopmental disorders with that of healthy children, using two anonymous surveys. Parents were asked to answer the survey from June 2020 to July 2021. Results: Out of 191 questionnaires obtained, 93 referred to parents in the Neurodevelopmental Disorder Group (NDG) and 98 to parents in the Control Group (CG). A total of 50.5% of parents in the NDG believed that their child's school performance improved when compared to the pre-pandemic period vs. 23.5% in the control group (p < 0.001). In terms of their overall health, 30.1% of the NDG parents reported that their child had been much better at home, compared to 9.2% of the CG parents (p = 0.001). There was a statistically significant improvement in family dynamics and relationships in the NDG, with 31.2% vs. 15.3% in the CG (p = 0.007). Discussion: This study portrays the impact of the lockdown and its consequences on children with ND. Parents in the NDG reported an improvement in their child's academic performance and in intra-family relationships. We found that most parents believed that access to schooling was insufficient with remote learning as well as access to therapies. There should be more measures and alternative strategies to minimize the impact that a lockdown has on children with special needs, especially among those in need of therapies. This study also emphasizes the importance of parents having an active role in the life of children with ND and achieving work-family balance. Further studies are needed to evaluate the real long-term impact of this period on children with neurodevelopmental disorders.